2008
DOI: 10.1071/sh07093
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of men in an Australian male tolerance study towards microbicide use

Abstract: Background Vaginal microbicides are in development to provide new options for prevention of STIs. Although promoted as a female initiated product, men may influence the decision to use a microbicide and the way that it is used, so it is important to explore their views. Methods Men (n=36) enrolled in a 7-day, phase 1 clinical safety trial of SPL7013 Gel were interviewed pre and post-use of the gel. The trial did not include use of the gel during sex. Interviews were digitally-recorded and transcribed verbati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Whilst women insert the gel and are directly controlling product use, men also have opinions over whether or not the product is acceptable. Studies have been conducted in Australia to assess the issue of microbicide acceptability with a cohort of men and issues including perceptions of safety, acceptance of the gel characteristics and partner disclosure were discussed (Holmes et al 2008;Rosenthal, Holmes, and Maher 2009). The male cohort in the study were mostly positive about the use of the gel and the authors point out that enhancing men's participation in such research will assist with the ongoing development of an important HIV-prevention product.…”
Section: Research Participationmentioning
confidence: 97%
See 1 more Smart Citation
“…Whilst women insert the gel and are directly controlling product use, men also have opinions over whether or not the product is acceptable. Studies have been conducted in Australia to assess the issue of microbicide acceptability with a cohort of men and issues including perceptions of safety, acceptance of the gel characteristics and partner disclosure were discussed (Holmes et al 2008;Rosenthal, Holmes, and Maher 2009). The male cohort in the study were mostly positive about the use of the gel and the authors point out that enhancing men's participation in such research will assist with the ongoing development of an important HIV-prevention product.…”
Section: Research Participationmentioning
confidence: 97%
“…Men have been involved in microbicide acceptability research in other contexts, including Australia where a tolerance study was carried out (Holmes, Maher, and Rosenthal 2008;Rosenthal, Holmes, and Maher 2009). A recent trial called IPREX successfully involved men who have sex with men in testing the efficacy of using emtricitabine and tenofovir as a pre-exposure prophylaxis to prevent HIV infection (Grant et al 2011).…”
Section: Men and Hiv-prevention Research In South Africamentioning
confidence: 98%
“…Though RM are currently intended for the receptive partner during anal intercourse, we did not screen for sexual role (insertive vs. receptive) since insertive partners may be involved in the application of the product in their partners and would also have opinions related to the product's attributes. A similar approach has been used in acceptability studies of vaginal microbicides [37].…”
Section: Procedures and Participantsmentioning
confidence: 97%
“…Perceived product efficacy (PPE) is a key feature driving the acceptability of, and potential adherence to, HIV/STI prevention products (Bass, 2002; Greene et al, 2010; Guest et al, 2007; Holmes, Maher, & Rosenthal, 2008; Mantell, Morar, Myer, & Ramjee, 2006b; Saethre & Stadler, 2010). PPE refers to a user’s perception of the extent to which a product is capable of producing a desired result.…”
Section: Introductionmentioning
confidence: 99%
“…These properties include physicochemical and rheological aspects of gel composition and performance, such as appearance, feel, flow, coating, and dilution effects. Although prior work has suggested that users’ opinions about product efficacy may be tied to microbicides’ physical properties (Holmes et al, 2008; Saethre & Stadler, 2010; Short, Mills, Majkowski, Stanberry, & Rosenthal, 2003; Short, Succop, Ugueto, & Rosenthal, 2007), no study has yet examined the specific user sensory perceptions and experiences, elicited by specific rheological and physicochemical properties, and how they might impact perceived product efficacy or use. These are critically important questions while microbicides are still in development; it is an opportune time to change aspects of product formulation and to prepare appropriate educational strategies to support microbicide users.…”
Section: Introductionmentioning
confidence: 99%